PENINGKATAN KEMAMPUAN PROBLEM SOLVING DAN DISPOSISI MATEMATIS SISWA SMA MELALUI PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK - Unni Marita; Edi Tandililing; Agung Hartoyo (Universitas Tanjungpura, 2020)
Abstract This research aimed to improve students' abilities of problem-solving and mathematical disposition by developing a lesson plan which was based on a scientific approach. The researcher analyzed the lesson plan developing process, the validity of the lesson plan's development result, its practicality/simplicity, the effectivity, and students' ability of problem-solving and mathematical disposition improvement which was the outcome of the lesson plan experiment. This research is a developmental study that refers to 4D models to science-three program XI grade students of SMA Muhammadiyah 1 Pontianak as the subjects of the research. The instruments which were used to collect the data in this research consist of the validation sheet, the field note of students' activities, the observation checklists of the procedure in the teaching and learning process, the test, and the questionnaires. The result of this research are: (1) the lesson plan used in this research was considered very valid; (2) the lesson plan was categorized as